Tissue‐engineered tendon nano‐constructs for repair of chronic rotator cuff tears in large animal models - Yonghyun Gwon; Woochan Kim; Sunho Park; Yang‐Kyung Kim; Hyoseong Kim; Myung‐Sun Kim; Jangho Kim (Bioengineering & Translational Medicine)
Abstract Chronic rotator cuff tears (RCTs) are one of the most common injuries of shoulder pain. Despite the recent advances in surgical techniques and improved clinical outcomes of arthroscopically repaired rotator cuffs (RCs), complete functional recovery—without retear—of the RC tendon through tendon‐to‐bone interface (TBI) regeneration remains a key clinical goal to be achieved. Inspired by the highly organized nanostructured extracellular matrix in RC tendon tissue, we propose herein a tissue‐engineered tendon nano‐construct (TNC) for RC tendon regeneration. When compared with two currently used strategies (i.e., transosseous sutures and stem cell injections), our nano‐construct facilitated more significant healing of all parts of the TBI (i.e., tendon, fibrocartilages, and bone) in both rabbit and pig RCT models owing to its enhancements in cell proliferation and differentiation, protein expression, and growth factor secretion. Overall, our findings demonstrate the high potential of this transplantable tendon nano‐construct for clinical repair of chronic RCTs.